(untitled) (CIPEEX, 2025)
The intensive use of digital technologies in the educational environment has generated significant impacts on students’ mental health. Hyperconnection, excessive screen time, and emergency remote teaching have brought to light issues related to anxiety, depression, and learning difficulties. Furthermore, inequality in access to technologies can exacerbate students’ emotional challenges. Objective: To investigate the impacts of excessive use of digital technologies on the mental health of higher education students, analyzing educational and technological strategies that can promote emotional well-being and the balanced use of digital media in the school environment. Method: The research was conducted through a literature review on the impact of digital technologies in the educational environment. Articles on active methodologies, educational technologies, emotional health in remote environments, and emotional support strategies mediated by Information and Communication Technologies (ICTs) were considered. Results: The studies analyzed demonstrated that excessive screen exposure can increase levels of anxiety, stress, and depression among students. However, strategies such as the use of active methodologies, collaborative digital learning environments, and emotional support through ICTs can mitigate these negative effects. Technologies such as artificial intelligence and digital platforms have the potential to support the development of socio-emotional skills and promote a more welcoming school environment. Conclusion: The use of digital technologies in the educational context must be balanced and combined with emotional support strategies. The promotion of innovative pedagogical practices and the integration of ICTs can contribute to a healthier and emotionally balanced learning environment.